A Comparative Study of Two Blast-Induced Traumatic Brain Injury Models: Changes in Monoamine and Galanin Systems Following Single and Repeated Exposure - Kawa, Lizan; Kamnaksh, Alaa; Long, Joseph B.; Arborelius, Ulf P.; Hökfelt, Tomas; Agoston, Denes V.; Risling, Mårten (Frontiers in Neurology, 2018)
Repeated mild blast-induced traumatic brain injury (rmbTBI), caused by recurrent exposure to low levels of explosive blast, is a significant concern for military health systems. However, the pathobiology of rmbTBI is currently poorly understood. Animal models are important tools to identify the molecular changes of rmbTBI, but comparisons across different models can present its own challenges. In this study, we compared two well-established rodent models of mbTBI, the “KI model” and the “USU/WRAIR model”. These two models create different pulse forms, in terms of peak pressure and duration. Following single and double exposures to mild levels of blast, we used in situ hybridization (ISH) to assess changes in mRNA levels of tyrosine hydroxylase (TH), tryptophan hydroxylase (TPH2), and galanin in the locus coeruleus (LC) and dorsal raphe nucleus (DRN). These systems and their transmitters are known to mediate responses to stress and anxiety. We found increased mRNA levels of TH, TPH2 and galanin in the LC and DRN of single-exposed rats relative to sham rats in the KI but not the USU/WRAIR model. Sham mRNA values measured in the USU/WRAIR model were substantially higher than their KI counterparts. Double exposure caused similarly significant increases in mRNA values in the KI model but not the USU/WRAIR model, except TPH2 and galanin levels in the DRN. We detected no cumulative effect of injury in either model at the used inter-injury interval (30 min), and there were no detectable neuropathological changes in any experimental group at 1 day post-injury. The apparent lack of early response to injury as compared to sham in the USU/WRAIR model is likely caused by stressors (e.g., transportation and noise) associated with the experimental execution that were absent in the KI model. This study is the first to directly compare two established rodent models of rmbTBI, and to highlight the challenges of comparing findings from different animal models. Additional studies are needed to understand the role of stress, dissect the effects of psychological and physical injuries and to identify the window of increased cerebral vulnerability, i.e., the inter-injury interval that results in a cumulative effect following repeated blast exposure.